A comparative study of nitrobenzene reduction using model catalysts. Issue 3 (19th December 2018) - Wu, Shuchang; Lin, Yangming; Zhong, Bingwei; Wen, Guodong; Liu, Hongyang; Su, Dang Sheng
Abstract : A zigzag-type quinone plays an important role in the reduction of nitrobenzene even in the co-existence of other functional groups. Abstract : A zigzag-type quinone performs better than an armchair-type quinone in the reduction of nitrobenzene. When different kinds of functionalities co-exist, the reaction is dominated by the most active sites, but the most negative sites should also be taken into consideration if the acitive sites have zigzag structures.